Toward the development of Mg alloys with simultaneously improved strength and ductility by refining grain size via the deformation process - Zhang, Zhi; Zhang, Jing-huai; Wang, Jun; Li, Ze-hua; Xie, Jin-shu; Liu, Shu-juan; Guan, Kai; Wu, Rui-zhi (International journal of minerals, metallurgy and materials, 2021)
Magnesium (Mg) alloys, as the lightest metal engineering materials, have broad application prospects. However, the strength and ductility of traditional Mg alloys are still relativity low and difficult to improve simultaneously. Refining grain size via the deformation process based on the grain boundary strengthening and the transition of deformation mechanisms is one of the feasible strategies to prepare Mg alloys with high strength and high ductility. In this review, the effects of grain size on the strength and ductility of Mg alloys are summarized, and fine-grained Mg alloys with high strength and high ductility developed by various severe plastic deformation technologies and improved traditional deformation technologies are introduced. Although some achievements have been made, the effects of grain size on various Mg alloys are rarely discussed systematically and some key mechanisms are unclear or lack direct microscopic evidence. This review can be used as a reference for further development of high-performance fine-grained Mg alloys.